Model Kaderisasi Ulama dan Da'i di Pondok Pesantren Darul Khair Pekanbaru dalam Menghadapi Revolusi Industri 4.0 - Dadang Firdaus; Kiki Cahya Muslimah; Ismail Ubaidillah (TADARUS, 2026)
This study examines the construction of ulama and da'i cadre formation at Pesantren Darul Khair Pekanbaru in the context of the Fourth Industrial Revolution. The analysis focuses on four central pillars, namely the strengthening of turats-based epistemology, the formation of moral habitus, the development of da'wah competence, and the implementation of a moderate digital adaptation strategy. Employing a descriptive qualitative approach, data were collected through participatory observation, in-depth interviews, and document analysis to capture the comprehensive mechanisms shaping religious authority within the pesantren. The findings reveal that Pesantren Darul Khair maintains its traditional identity while simultaneously developing adaptive strategies that align with the dynamics of contemporary digital society. The model identified in this study demonstrates that the continuity of pesantren traditions can coexist with the enhancement of intellectual, moral, social, and digital competencies among students. This research contributes theoretically to the concept of adaptive religious authority and offers practical implications for strengthening Islamic boarding school education in the era of digital transformation.